Achieving High‐Voltage and High‐Capacity Aqueous Rechargeable Zinc Ion Battery by Incorporating Two‐Species Redox Reaction. Issue 45 (25th October 2019) - Ma, Longtao; Chen, Shengmei; Long, Changbai; Li, Xinliang; Zhao, Yuwei; Liu, Zhuoxin; Huang, Zhaodong; Dong, Binbin; Zapien, Juan Antonio; Zhi, Chunyi
Abstract: Herein, a two‐species redox reaction of Co(II)/Co(III) and Fe(II)/Fe(III) incorporated in cobalt hexacyanoferrate (CoFe(CN)6) is proposed as a breakthrough to achieve jointly high‐capacity and high‐voltage aqueous Zn‐ion battery. The Zn/CoFe(CN)6 battery provides a highly operational voltage plateau of 1.75 V (vs metallic Zn) and a high capacity of 173.4 mAh g −1 at current density of 0.3 A g −1, taking advantage of the two‐species redox reaction of Co(II)/Co(III) and Fe(II)/Fe(III) couples. Even under extremely fast charge/discharge rate of 6 A g −1, the battery delivers a sufficiently high discharge capacity of 109.5 mAh g −1 with its 3D opened structure framework. This is the highest capacity delivered among all the batteries using Prussian blue analogs (PBAs) cathode up to now. Furthermore, Zn/CoFe(CN)6 battery achieves an excellent cycling performance of 2200 cycles without any capacity decay at coulombic efficiency of nearly 100%. One further step, a sol–gel transition strategy for hydrogel electrolyte is developed to construct high‐performance flexible cable‐type battery. With the strategy, the active materials can adequately contact with electrolyte, resulting in improved electrochemical performance (≈18.73% capacity increase) and mechanical robustness of the solid‐state device. It is believed that this study optimizes electrodes by incorporating multi redox reaction species for high‐voltage and high‐capacity batteries. Abstract : Although the Prussian blue analogues are widely used as cathode for aqueous metal‐ion batteries, their specific capacity is limited to ≈60 mAh g −1, due to only single electrochemically activated species of transition‐metal ions. Herein, a two‐species redox reaction of Co(II)/Co(III) and Fe(II)/Fe(III) incorporated in cobalt hexacyanoferrate is proposed as a breakthrough to achieve jointly high‐capacity and high‐voltage aqueous Zn‐ion battery.